Invigorating diabetes care in a post-pandemic arena. Issue Volume 33:Issue suppl 3(2022) (1st March 2022) - Phillips, Anne
Abstract : Diabetes services have undergone significant changes during the pandemic. Anne Phillips highlights the opportunities this provides for improving care for people living with diabetes